2017
DOI: 10.3389/fnmol.2017.00272
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Differences in Blood Plasma Associated with Antidepressant Treatment Response

Abstract: The current inability of clinical psychiatry to objectively select the most appropriate treatment is a major factor contributing to the severity and clinical burden of major depressive disorder (MDD). Here, we have attempted to identify plasma protein signatures in 39 MDD patients to predict response over a 6-week treatment period with antidepressants. LC-MS/MS analysis showed that differences in the levels of 29 proteins at baseline were found in the group with a favorable treatment outcome. Most of these pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Further, elevated proteoforms of hemopexin have been found in farmers with musculoskeletal disorder 35 . In addition, several proteomic studies of major depressive disorder have been conducted, revealing proteins to be involved in similar processes presented in this study, mainly acute-phase, blood coagulation, and immunity [51][52][53] . These studies indicate that the immune system and its proteins might be affected by elevated depression.…”
Section: Discussionmentioning
confidence: 64%
“…Further, elevated proteoforms of hemopexin have been found in farmers with musculoskeletal disorder 35 . In addition, several proteomic studies of major depressive disorder have been conducted, revealing proteins to be involved in similar processes presented in this study, mainly acute-phase, blood coagulation, and immunity [51][52][53] . These studies indicate that the immune system and its proteins might be affected by elevated depression.…”
Section: Discussionmentioning
confidence: 64%
“…Turck et al [41] showed that differences in the levels of 29 proteins at baseline were found in the group with a favorable treatment response, where most of these proteins were components of metabolism or immune response pathways as well as multiple components of the coagulation cascade. After the treatment period, 2 proteins that were altered in responders and 9 in nonresponders overlapped with those proteins that had been identified in the baseline group [41]. Of this, the fibrinogen alpha chain was 1 of the 9 altered proteins in nonresponders as shown by our group [42].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…However, some plasma biomolecules have been reported as potential biomarkers for MDD. For example, apolipoprotein D and ceruloplasmin have been reported to be associated with changes in lipid metabolism and immunoregulation in MDD patients [ 1 , 2 , 3 ]. The concentrations of lipids such as carnitine C10:1 and PE-O 36:5 were shown to be downregulated, while the concentration of LPE 18:1 sn-2 appeared upregulated in MDD patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%